Application of chitosan biopolymer as a sensing material - Roshida binti Mustaffa (School of Materials Engineering, Universiti Malaysia Perlis, 2009)
The chitosan solution has been succesfully deposited on the silicon wafer using sol-gel method to fabricate the chitosan thin film sensors. The effect of different annealing temperature and annealing time to their electrical characteristics were studied without and under light illumination. The current-voltage (I-V) characteristics showed that sensitivity of chitosan thin film sensors depend on the annealing temperature and annealing time. For the annealing temperature effect, it was found that the film annealed at 190oC has the highest photocurrent compared to the others. While for the annealing time effect, it was shown that the higher annealing time, the higher photocurrent. The changes of photocurrent are related to the different microstructure of chitosan thin film sensors. Although, the photocurrent values of the films illuminated with light exhibit the fluctuation to the photocurrent values without light illumination. Overall the chitosan thin films are sensitive to the visible and UV light. Therefore, they have a good potential as thin film light sensors.